Forgotten status of many: Kosovo's economy under the UN and the EU administration - Isa Mulaj (OrdnungsPolitisches Portal (OPO), 2007)
After eight years of the United Nations (UN) administration, Kosovo again is returned to the international centre of attention - this time about her future political status. The document presented by the UN Special Envoy for Kosovo, Martti Ahtisaari, proposed an ambiguous status settlement that is portrayed and understood as a supervised independence. Whatever expectations from political perspective will be, that is of secondary importance for this paper - the aim is in Kosovo's aggregate uncertainty about her economic sustainability, namely to investigate the relationship between fragile institutions, poor governance and weak economic performance. With a foreign aid since the second half of 1999 amounting to exteuro22 billion, Kosovo still has massive unemployment and widespread poverty. How the UN's largest experiment ever undertaken, involving considerable resources and long time, left the economy in such a poor state?
Keywords: 330; Kosovo; UNMIK; Provisional Institutions of Self-government; poverty; political status settlement